ANALISIS PERANGKAT PEMBELAJARAN GURU PENDIDIKAN AGAMA ISLAM BERDASARKAN KURIKULUM 2013 DI SMP NEGERI 1 PERCUT SEI TUAN DELI SERDANG - Nur Aini (Universitas Islam Negeri Sumatera Utara Medan, 2019)
The purpose of this study was to determine: (1) Suitability of 2013Curriculum Annual Program Preparation, (2) Suitability of Compilation ofthe 2013 Curriculum Semester Program. (3) Appropriate components ofthe Learning Implementation Plan (RPP) based on Permendikbud No.222016. The approach used in this study is a qualitative approach The dataanalysis technique used is data collection, data reduction and data presentation conclusions. The technique of guaranteeing the validity of the data is done by checking trust, checking examination and checkingdependency. The results of the study can be concluded that the results ofthe Analysis of Suitability of Annual Programming, Semester Program,and Learning Implementation Plan can be categorized as